A model for adoption of ICT in Jordanian higher education institutions: An empirical study - Khasawneh, Mohammad M.F.; Ibrahim, Huda (IBIMA Publishing, 2012)
Information and Communication Technology (ICT) plays a major role in modern universities by facilitating and improving the educational system to be in line with the information technology age.The higher education sector in Jordan is considered as one of the most influential sectors that develop the country.In striving towards a competitive institution, a university must enhance teaching and learning process related to the advancement of ICT.However, this study attempts to focus on the adoption of ICT in Jordanian public universities among the academic staff, with the concern on the factors influencing their acceptance of ICT in the educational system.Moreover, the study attempts to build a conceptual model to the Jordanian case according to the results of factor analysis.A self administrated survey was conducted on 500 teaching staff selected from public universities in Jordan. A total of 415 participants (83%) have responded, and series of data analyses of variables measurement for reliability and validity test of predictors were performed.The results of the analysis, however, contribute a new model which is considered as a novel model in such studies.